Correlation of Air Lead Level and Respondent Characteristics Toward Blood Lead Level Among Pedicab Drivers in Gresik - Nur Lathifah Syakbanah (JURNAL KESEHATAN LINGKUNGAN, 2018)
Lead (Pb) is one of harmful pollutants for human health and environment. Therefore, the aim of study was to describe of air lead level and respondent characteristics toward blood lead level among pedicab drivers in Sukomulyo Street and Dr. Wahidin Sudirohusodo Street, Gresik Regency. It was an observational-analytical study using cross sectional design. Dependent variables was blood lead level, independent variables were air lead level, respondent characteristics include age, work period, smoking habit and number of cigarettes. Subjects were using snowball sampling 9 pedicab drivers on Sukomulyo Street and Dr. Wahidin Sudirohusodo Street. Data collection was using questionnaire, air lead level and blood lead level laboratory results. Data analysis was using descriptive. Result shows that air lead level were 1.69 í— 10-4 and 1.60 í— 10-4 mg/m3. Mean ± standard deviation among pedicab drivers in Sukomulyo Street and Dr. Wahidin Sudirohusodo Street for blood lead level (6.14 ± 0.51 Î¼g/dl; 5.92 ± 0.18 Î¼g/dl), age (59.20 ± 16.25 years; 44.75 ± 19.28 years), work period (24.00 ± 25.68 years; 4.00 ± 2.58 years), smoking habit (75.00%; 80.00%), number of cigarettes (> 10 cigarettes per day). It is concluded that air lead level and blood lead level fulfill limit value. It is suggested to choose rest area around roadside plants which is absorbing lead and consume calcium milk, routinely.